Combined endoscopic transethmoid and transconjunctival en bloc resection of optic nerve tumors in patients lacking functional vision - Shi, Jieliang; Tu, Yunhai; Xu, Mingna; Wu, Wencan (Frontiers in Oncology, 2022)
Background: Surgical treatment of optic nerve tumors is challenging. The study’s objective was to evaluate the efficacy of a combined endoscopic transethmoid and transconjunctival approach in patients without functional vision. Design: A retrospective, noncomparative case series. Methods: Retrospective data were collected from all patients who had undergone tumor resection using this approach at the authors’ institution between 2015 and 2021. Preoperative assessments included magnetic resonance imaging and ophthalmological examinations, and re-assessments were conducted three months after surgery and regularly during the follow-up period. Results: Seventeen patients, mean age 35 ± 19.0 years, were enrolled. Of these, 64.7% presented with visual acuity (VA) of light perception or no light perception. Gross total resection was realized in all patients. The average decline in exophthalmos was 3.63 ± 1.93 mm. Tumor histopathological analysis identified 12 optic nerve sheath meningiomas and 5 optic gliomas. The mean follow-up time was 30 months during which there was no local recurrence in any of the patients. Conclusions: The combined endoscopic transethmoid and transconjunctival approach offers an additional choice for accessing optic nerve tumors. The procedure is both safe and effective and provides an alternative transcranial route to the orbit.